Reporting social behaviours of mixed-species troops formed by Callithrix jacchus and Callithrix penicillata (Primate, Callitrichidae) - Valenca-Silva, Graziela [UNESP]; Maciel, Fernanda de Góes; Zaganini, Rosangela Lopes [UNESP]; Lucindo, Anderson da Silva; Caramaschi, Sandro [UNESP]; Paula, Hugo Medeiros Garrido de (Int Inst Ecology, 2014)
In New World primates, mixed-species troops have been reported. Here, we analysed the performance of affiliative and agonistic behaviours of Callithrix jacchus and Callithrix penicillata living in mixed groups. For this purpose, we recorded the interaction of the individuals from two groups located in Bauru city, in the state of Sao Paulo (Brazil). Our data show that in both groups, affiliative behaviours appeared more frequently than agonistic ones. We concluded that there is cohesion inside the mixed-species troops observed. We suggest that a deeper knowledge about the social behaviour of mixed-species troop species certainly may be useful in projects linked with the management of the impact caused by them.

Grupos mistos em espécies de primatas do Novo Mundo têm sido relatados. Aqui, nós avaliamos a emissão de comportamentos afiliativos e agonísticos em grupos mistos formados por Callithrix jacchus e Callithrix penicillata. Para tanto, registramos a interação de dois grupos, localizados no município de Bauru, Estado de São Paulo (Brasil). Nossos dados mostram que nos dois grupos a emissão de comportamentos afiliativos foi maior do que a de comportamentos agonísticos, indicando que há coesão dentro dos grupos mistos estudados. Sugerimos que um conhecimento mais elaborado sobre o comportamento social de grupos mistos pode ser útil em projetos de impactos causados por espécies invasoras.
Comportamento social em grupos mistos de Callithrix jacchus e Callithrix penicillata (Primate, Callitrichidae)
Keywords: Common marmoset; Black-tufted-ear marmoset; Social behaviour; Hybrid; Cohesion; Invasive species; Sagui-de-tufo-branco; Sagui-de-tufo-preto; Comportamento social; Híbridos; Coesão; Espécies invasoras